Comparison of the microbiological milieu of patients randomized to either hydrophilic or conventional PVC catheters for clean intermittent catheterization. Issue 3 (June 2016) - Lucas, Elizabeth J.; Baxter, Cheryl; Singh, Chandra; Mohamed, Ahmad Z.; Li, Birong; Zhang, Jingwen; Jayanthi, Venkata R.; Koff, Stephen A.; VanderBrink, Brian; Justice, Sheryl S.
Summary: Introduction: Control of bacteriuria is problematic in patients who perform clean intermittent catheterization for management of neurogenic bladder. This population is often burdened with multiple urinary tract infections (UTIs), placing them at increased risk of end-stage renal disease. Hydrophilic catheters are a potential way to improve smooth and clean insertion, reduce disruption of the urothelium, and reduce bacterial colonization. Objective: The goal of the study was to compare the type and virulence of microorganisms recovered from the urine of patients that use either a hydrophilic or conventional polyvinyl chloride (PVC) catheter. Methods: Fifty patients with an underlying diagnosis of myelomeningocele were recruited for a 12-month prospective, randomized, investigator-blinded study. Twenty-five patients were allocated to the hydrophilic catheter intervention, and 25 continued use of a PVC catheter. Cultures were performed on urine obtained by catheterization at enrollment, and 3, 6, and 12 months. Bacterial species were assigned a designation as either potentially pathogenic or non-pathogenic. Escherichia coli isolates were the most predominant and were serotyped to further stratify the pathogenicity of the strains. Lastly, patients were surveyed at enrollment, and at the two later time points evaluating their current catheter for satisfaction. Results: A total of 232 different bacterial isolates were obtained from the 182 collected urine cultures. In addition, seven species were recovered from the two UTI reported during the study period. Bacterial growth was not detected in 29 of the samples (16%). Although not statistically significant, collectively there was a 40% decrease in the average number of potentially pathogenic species recovered from those patients using hydrophilic catheters (0.81 per urine sample) compared with PVC catheter use (1.24 per urine sample). Since E. coli species can be either pathogenic or non-pathogenic, we examined 14 of the most commonly implicated serotypes associated with uropathogenic E. coli (UPEC). We identified the serotype of 57% of E. coli strains recovered. There was a trend for the recovery of fewer UPEC serotypes from the hydrophilic group (54% hydrophilic verses 64% PVC), further suggesting that the catheter type may influence the microbiological milieu. Although no significant differences were reported in patient satisfaction, almost half of the patients from the hydrophilic catheter cohort continue use of this type of catheter. Conclusions: There was a trend for reduced recovery of potentially pathogenic bacteria with the use of hydrophilic catheters. The reduction in potentially pathogenic species will reduce antibiotic exposures and some patients may prefer the comfort hydrophilic catheters provide. Figure Overview of the study. Fifty myelomeningocele patients were randomized to either the intervention of using a hydrophilic catheter for 12 months or to continue their PCV catheter; urine cultures were examined at 3-month intervals. At the end of the study, hydrophilic catheter users had fewer potential pathogenic species recovered from their cultures. Some individuals preferred the new catheters so much so they switched indefinitely.